Automation in Civil Engineering Design in Assessing Building Energy Efficiency - Khairulzaman, Hanis Adibah; Usman, Fathoni (International Journal of Engineering and Technology, 2018)
Automation in Civil Engineering design is no longer unfamiliar anymore in the construction industry. It brings great efficiency gains and has reduced many of the complicated aspects of design. Automation has been developing since over the last four decades where advancement of computer hardware and in line with software developments has enabled various sort of design to be computerized. The design process is now more fast and accurate, and the entire process has been outstandingly improved by the available technology. However, the problems related to computerized design, started from the possibilities for unrecognized or unanticipated consequences as the design becomes more complicated. In line with it is the global warming issue that has been threatening the human being. Therefore, this paper reviews the design automation and its application in civil engineering design emphasizing in assessing the energy efficiency of buildings, which includes background information, its application, advantages, and challenges and also suggestions to further improve the automation in civil engineering design by artificial intelligence (AI). It was discovered that since over the past few years, BIM implementation in Civil Engineering design has started to be adopted massively in construction industry due to its tremendous advantages. In this paper, a new flow process in design automation in assessing building sustainability has been proposed by implementing AI BIM which is linked with MyCREST, a green rating tool in Malaysia in order to assist designers to conceptually design for a more energy efficient building.